The Influence of Omni-Channel Integration Quality and Transactional Interest on Repurchase Decisions with Trust as a Mediating Variable at PT Pegadaian in the Perspective of Islamic Business - Elviani, Elviani; Habibi, Ahmad; Susanti, Yeni (CV. Civiliza Publishing, 2025)
This study comprehensively examines the impact of omni-channel integration quality and transactional interest on repurchase decisions, with trust as a mediating variable from the perspective of PT. Pegadaian UPC Pahoman Bandar Lampung customers, which is relevant to Islamic business principles. The methodology used is a quantitative approach, which is a scientific approach focused on the systematic collection and processing of numerical data from a defined population. The number of respondents was determined using the Slovin formula with a margin of error of 10%, resulting in a sample of 96 respondents who were active customers during the year 2024. The research results indicate that the quality of omni-channel integration and transactional interest have a positive and significant influence on the decision to make repeat purchases. In addition, the path analysis results reveal that trust plays a strong mediating role in strengthening the correlation between the independent variables and the decision to repurchase. This illustrates that in the context of Islamic business, the success of long-term relationships between companies and customers is highly dependent on the establishment of mutual trust and the fulfillment of the values of fairness, transparency, and integrity in every transaction interaction.